Case Report: Acute generalized exanthematous pustulosis with psoriasis successfully treated with Secukinumab - Zheng, Ji-Na; Liu, Xinying; Shi, Yuling; Gu, Jun; Gong, Yu (Frontiers in Immunology, 2025)
BackgroundAcute generalized exanthematous pustulosis (AGEP) is a rare but severe cutaneous adverse reaction characterized by the abrupt onset of non-follicular sterile pustules on an erythematous and edematous background. These pustules typically appear within 24 to 48 hours after exposure to the causative drug, often localized to the face, trunk, and intertriginous area. Herein we firstly reported a 56-year-old man with severe plaque psoriasis who developed metamizole-induced AGEP during a clinical trial for BEBT-305 (HSP90 inhibitor) that was successfully treated with Secukinumab.Case summaryA 56-year-old man with a 40-year history of severe plaque psoriasis developed fever and self-administered metamizole. Within a few days, a progressive eruption appeared and worsened until hospital admission with a baseline PASI score of 50.3 three weeks later. The rash was characterized by diffuse erythema, intense pruritus and severe desquamation. Additionally, he developed edema in the lower extremities, and dense pustules appeared on his neck, inner thighs, and abdomen. The patient had no history of systemic treatment for psoriasis and had only used topical agents with limited benefit prior to presentation. Previously, the patient was enrolled in the “Heat shock proteins 90 inhibitors BEBT-305 Clinical Trial (CTR20222218)”. The patient took BEBT-305–200 mg orally daily for one month with no adverse effect. The patient had no prior medical history and no known drug allergies. Further tests and examination showed a high white blood cell count and C-reactive protein, abnormal liver function. The IL36RN and CARD14 gene tests were negative. A diagnosis of AGEP was made, allowing for the administration of Secukinumab 300 mg by subcutaneous injection. Sustained improvements were seen 1 week after the first dose of subcutaneous injection with the PASI score decreased to 11.8. Of note, there was resolution of the pustules and most erythema. After discharge, the patient received monthly injections of secukinumab 300 mg for seven months. PASI 100 response was achieved at 7 months. All skin lesions have cleared, with no recurrence to date.ConclusionThis case is the first case in which metamizole-induced AGEP with a history of psoriasis has been successfully treated with Secukinumab. Biologics should be considered in patients with AGEP, especially those with a history of psoriasis. This can benefit both diseases.